Jogos eletrônicos e ensino de física: potenciais e possibilidades - Costa, Oaní da Silva da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work we present a um experience report of two didactic interventions in schools in the city of Rio Claro - SP, Brazil, using video games in Physics teaching activities at the Basic Education level. We used the game Screamride (FRONTIER DEVELOPMENTS, 2015) for Xbox One in a workshop to teach about energy topics and the game Angry Birds Space (ROVIO ENTERTAINMENT, 2012) for Android e IOS in a class to teach gravity topics inside the classroom. We observed that the didactic activities realized produced positive results when compared to the traditional Physics classes found in this educational stage, generally expositive, and that in the reported cases the video games contributed to teach Physics. Games can be useful for teaching. They can be used to explore Physics either rightfully or wrongly applied in them and should not be ignored in activities that aim the improvement of the quality of the Basic Education

Neste trabalho apresentamos um relato de experiência de duas intervenções didáticas em escolas de Rio Claro - SP, Brasil, utilizando video games em atividades de Ensino de Física para a Educação Básica. Trabalhamos com o jogo Screamride (FRONTIER DEVELOPMENTS, 2015) para Xbox One em uma oficina para ensino de tópicos de energia e o jogo Angry Birds Space (ROVIO ENTERTAINMENT, 2012) para Android e IOS em uma aula para ensino de tópicos de gravitação em sala de aula. Observamos que as experiências didáticas realizadas produziram resultados animadores quando comparados às aulas tradicionais de Física nessa faixa escolar, em geral expositivas, e que nesses casos o video game contribuiu para o ensino. Games podem ser úteis para o aprendizado seja na exploração de eventuais erros ou acertos de Física. Games são ferramentas possíveis para o ensino de Física e não deveriam ser ignorados em atividades que busquem a melhora da qualidade da Educação Básica
Keywords: Física - Estudo e ensino; Ensino - Meios auxiliares; Jogos eletronicos; Video games